Paradis - Thomasson, Oriane (The Eriskay Connection, 2022)
A cabinet of curiosities ? or Wunderkammer ? exhibits a wide variety of objects and artefacts with a particular notion towards the rare, eclectic and esoteric. Through their selection of objects, they tell a particular story about the way humans see the natural and cultural world.00Inspired by this way of collecting, Oriane Thomasson (FR) created Paradis, where science and art, natural and artificial, come together to produce a new fiction. The collection is a mosaic of photographic work and archival materials. From images she made during her travels through the Far East, to botanical and mineralogical illustrations.00Paradis examines the different materialities of images and the way they influence our imagination. The work questions the concept of nature through its representations, and the myths from Western societies that stem from those. As a modern explorer, Thomasson brings together what she discovered and assembles the images into a new narrative through which we wander.00Woven through the images is a fictional text in which the reader is led to an unknown land, as an explorer discovering mysterious and unknown lands. Paradis is an invitation to rediscover nature?s ability to make us imagine, dream and build new stories